Hypertension in Northern Angola: prevalence, associated factors, awareness, treatment and control - Pires, João E; Sebastião, Yuri V; Langa, António J; Nery, Susana V (BMC public health, 2013)
Seventy-five million people are estimated to be hypertensive in sub-Saharan Africa. This translates in high morbidity and mortality, as hypertension is now considered to be the number one single risk factor for death worldwide. Accurate data from countries lacking national disease surveillance is needed to guide future evidence-driven health policies. The authors aimed to estimate the prevalence, awareness, management and control of hypertension and associated factors in an adult population of Angola. A community-based survey of 1,464 adults, following the World Health Organization's Stepwise Approach to Chronic Disease Risk Factor Surveillance, was conducted to estimate the prevalence of hypertension, awareness, treatment and control in Dande, Northern Angola. Using a demographic surveillance system database, a representative sample of subjects, stratified by sex and age (18-40 and 41-64 years old), was selected. Prevalence of hypertension (systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg and/or hypertensive therapy) was of 23% (95% CI: 21% to 25.2%). A follow-up consultation confirmed the hypertensive status in 82% of the subjects who had a second measurement on average 23 days after the first. Amongst hypertensive individuals, 21.6% (95% CI: 17.0% to 26.9%) were aware of their status. Only 13.9% (95% CI: 5.9% to 29.1%) of the subjects aware of their condition were under pharmacological treatment, of which approximately one-third were controlled. Older age, lower level of education, higher body mass index and abdominal obesity were found to be significantly (p<0.01) associated with hypertension. Our survey is the first to provide insightful data on hypertension prevalence in Angola. There is an urgent need for strategies to improve prevention, diagnosis and access to adequate treatment in this country, where a massive economic growth and consequent potential impact on lifestyle risk factors could lead to an increase in the prevalence of hypertension and cardiovascular disease.